Tax Effects on Unemployment and the Choice of Educational Type - Annette Alstadsæter; Ann-Sofie Kolm; Birthe Larsen (Statistics Norway, Research Department, 2005)
This paper examines the effect of taxes on the individuals' choices of educational direction, and thus on the economy's skill composition. A proportional labour income tax induces too many workers with high innate ability to choose an educational type with high consumption value and low effort costs. This increases the skill mismatch and aggregate unemployment in the economy. The government can correct for this distortion by use of differentiated tuition fees or tax rates.
Keywords: J64; J68; H21; H24; 330; Unemployment; matching; education; optimal taxation; tuition fees